Unveiling the Tapestry of Machine Learning: From Basics to Advanced Applications - Anand R. Mehta, Srikarthick Vijayakumar (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2018)
As the expedition progresses, we ascend to the forefront of innovation—neural networks and deep learning. Architectural intricacies, from convolutional neural networks revolutionizing image recognition to recurrent neural networks mastering sequential data, are laid bare. The narrative extends to the challenges that permeate the field, including the specters of overfitting, bias, and ethical considerations. This article transcends theoretical discourse, weaving in practical applications across diverse domains. Case studies illuminate machine learning’s prowess in healthcare diagnostics, financial predictions, and the burgeoning realm of autonomous vehicles. Recent strides in transfer learning, reinforcement learning’s foray into real-world problem-solving, and synergies with natural language processing adorn the fabric of our exploration. In synthesizing the fundamentals with the avant-garde, this article offers a comprehensive tapestry of machine learning’s evolution, making the complex accessible and paving the way for future endeavors in this dynamic field.